Activity of Argemone Ochroleuca Extract On the in Vitro Viability of Cutaneous Leishmaniasis Promastigotes Comparison to Sodium Stibogluconate Drug - AL- Qormuti, Sanya abdulkareem; Alhatemi, Noman Ahmed Yahya; Alosoufe, Laith; Al-awj, Sala mohammed; Alsalahi, Almanwar mohammed; Albukhaiti, Gubran hamid; Shamsan, Taiseer Abdul-raheem; Alhogami, Haneef Hasan; Al-Fakih, Muhannad Abdulkawi Ali; Al-Shehri, Shaima Taher; Ibraheim, Marwa Mohamad (International Journal of Membrane Science and Technology, 2023)
This study investigates the inhibitory activity of Argemone ochroleuca leaf plant extracts which was so prepared by using different solvents (ethanol, methanol, and distilled water) on the in vitro viability of cutaneous leishmaniasis promastigotes, in comparison with the established drug sodium stibogluconate.Cutaneous leishmaniasis, caused by Leishmania parasites, poses significant health challenges globally. Conventional treatments, like sodium stibogluconate, have limitations such as toxicity and drug resistance. Plant extracts, owing to their diverse bioactive constituents, present a potential alternative for disease management.Argemone ochroleuca plant extracts were prepared using ethanol, methanol, and distilled water as solvents. The inhibitory effect on promastigote viability was assessed using a time-based approach, measuring the duration in seconds that is required for inhibition to occur. Interestingly, at certain concentrations, the extract exhibited comparable or even superior efficacy to sodium stibogluconate. Results were compared with the inhibitory effect of sodium stibogluconate. The findings demonstrate the following inhibitory times for Argemone ochroleuca plant extracts: Ethanol: Inhibition occurred at 400 mg/ml in 9 seconds, at 200 mg/ml in 26 seconds, at 100 mg/ml in 60 seconds, and at 50 mg/ml in 128 seconds, Methanol: Inhibition occurred at 400 mg/ml in 13 seconds, at 200 mg/ml in 39 seconds, at 100 mg/ml in 91 seconds, and at 50 mg/ml in 210 seconds and Aquatic extract: Inhibition occurred at 400 mg/ml in 94 seconds, at 200 mg/ml in 150 seconds, at 100 mg/ml in 258 seconds, and at 50 mg/ml in 474 seconds. Comparatively, sodium stibogluconate showed its inhibitory effect at a specific concentration 100 mg/ml in 10 second.These results indicate that the Argemone ochroleuca leaves plant extracts, particularly those prepared using ethanol and methanol, exhibit substantial inhibitory effects on the viability of cutaneous leishmaniasis promastigotes. The variations in inhibitory times among the solvents suggest differences in the bioactive compound extraction and interactions. Ethanol and methanol extracts present potential alternatives to conventional treatments, with faster and efficient inhibitory action.Further research is warranted to elucidate the specific bioactive compounds responsible for these inhibitory effects and to explore the underlying.